2008
DOI: 10.3146/ps08-003.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resistance to Cylindrocladium Parasiticum of Runner-Type Peanut in The Greenhouse and Field

Abstract: Identification and utilization of peanut cultivars with resistance to Cylindrocladium black rot (CBR) is a desirable approach to manage this disease. The objectives of this study were to improve greenhouse and field screening techniques for resistance to CBR, and to evaluate the reaction of selected runner-type peanut genotypes. Georgia-02C (moderately resistant to CBR) and C-99R (CBR-susceptible) were used in comparing the effectiveness of different inoculation methods in the greenhouse. Disease development w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…However, differences in plant condition rating associated with CBR were noted for cultivars (p 5 0.0038), with VA 98R expressing more disease than Perry (12% versus 5%, data not shown in tables). The cultivar VA 98R is more susceptible to CBR than the cultivar Perry (Dong et al, 2008;Isleib et al, 2003;Mozingo, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…However, differences in plant condition rating associated with CBR were noted for cultivars (p 5 0.0038), with VA 98R expressing more disease than Perry (12% versus 5%, data not shown in tables). The cultivar VA 98R is more susceptible to CBR than the cultivar Perry (Dong et al, 2008;Isleib et al, 2003;Mozingo, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Effect of container size (CN), Cylindrocladium parasiticum inoculum density (DN) (microsclerotia/g soil (ms)), and week (WK) of sampling on resistant (NC 3033 = R) and susceptible (NC 7 = S) peanut genotypes for each disease assessment method in trial II. disregarded potential violations of assumptions and analyzed data using analysis of variance rather than employing non-parametric tests (Dong et al, 2008;Hollowell et al, 2008). Our research demonstrates that taproot necrosis measurements are a valid alternative to root rot ratings.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was still variability in severity from trial to trial. The variability between trials is likely due to the different sizes of sclerotia that are counted or not counted due to a continuum of microsclerotia sized (Dong, 2008) and/or changes in isolate aggressiveness between trials. Pataky et al (1983) suggested that pronounced differences in the response of Florigiant to increasing inoculum densities between trials were a result of changes due to long term storage of C. parasiticum cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations